(untitled) (Journal of Hama University, 2022)
The research aims to clarify the concept and methods of the analytical tax audit procedures, and to determine the trends of income auditors about the contribution of analytical audit procedures to reducing tax evasion, in addition to studying the differences between the income auditors’ answers about the contribution of analytical audit procedures to reducing tax evasion. The research is based on the descriptive and analytical approaches, and a questionnaire was directed to workers in the General Authority for Taxes and Fees of the Ministry of Finance aimed at measuring the contribution of analytical audit procedures to reducing tax evasion. The study reached several results, the most important of which are: that there is an impact of the data and information available to the tax administration, and there is an impact of the obstacles facing tax auditors in using analytical audit procedures to reduce tax evasion, and that historical and comparison with other establishments, vertical analysis processes and studying the relationship between information play a key role In reducing the level of tax evasion, and that the use of analysis procedures in several stages (planning, auditing, preparing the statement) may play a negative role in reducing tax evasion, and that there are fundamental differences between the answers of income controllers about the contribution of the analytical audit procedures in reducing evasion. Taxes according to the number of years of experience and position.